Advancing Electrical Technology Education: Investigating the Impact of Immersive Simulation Tools on Hands-On Learning Outcomes - Borromeo, Christian Guiane G.; Fabro, Regie Boy B.; Juan, Shiela Mae G.; Daquioag, Dariel Justin V.; Ladran, Peter John P.; Blanco, Johnson Modesto A.; Balintec, Christian Jeffrey G. (Future Science / FSH-PH Publications, 2025)
This study investigates the effectiveness of immersive simulation tools in enhancing hands-on learning, engagement, and practical skills among Bachelor of Technical Vocational Teacher Education (BTVTEd) Electrical Technology students. Recognizing the challenges of traditional laboratory-based training, such as safety risks, limited resources, and restricted practice opportunities, the study explores how immersive technologies can address these limitations. Utilizing a mixed-methods research design, the study combines quantitative approaches, including pre-test and post-test assessments and surveys, with qualitative methods, such as focus group discussions and semi-structured interviews, to comprehensively evaluate the tools' impact. Conducted in a teacher education institution in Ilocos Norte, the study involves third-year electrical technology students and their instructors. Results indicate that immersive simulation tools significantly improve students’ practical skills, as evidenced by a statistically significant increase in post-test scores. Both students and instructors perceive these tools as highly effective and user-friendly, emphasizing their ability to simplify complex concepts, enhance skill acquisition, and foster confidence. The tools also provide realistic and safe environments for practicing high-risk tasks, such as working with high-voltage equipment, reducing safety concerns while promoting deeper learning. However, challenges such as technical issues, limited access to equipment, high costs, and the need for training are identified as barriers to broader adoption. The study concludes that immersive simulation tools are a transformative innovation in technical education, offering safer, more engaging, and effective learning experiences.